Use of temperature for diagnosing mixing in the IsaMill - Gunda, Ronald (My University, 2014)
The IsaMill is a recently developed process equipment , first commissioned on a large scale in the early 90s in an effort to help recover values from old mine dumps due to improvements in downstream extraction technologies which could further recover values from ores with fine particles, a technology which was not available before. Also due to depletion of easy-to-extract ores and prevalence of fine grained ores which cannot be economically liberated using the traditional mills like ball mills , there was need to develop a mill that could grind ore to sizes of the order of less than 20 micrometres; hence the evolution of the Isamill. As this is a recent technology, limited research has been done to fully characterise this mill, important to mineral processing economics as it is Milling efficiency and operation of the plant can be improved if the degree of mixing in the mill can be reduced as that reduces overgrinding or under grinding. A clearer understanding of the mill dynamics will help in coming up with better understanding of mill operations which will assist in developing better mill design and control philosophies. An M4 pilot IsaMill with overall length 393mm and internal diameter 135mm was used for the test work. Temperature measurements were used to identify the mixing process in the mill. Ten resistance temperature devices (RTDs) were inserted along the length of the mill from feed to discharge. Holes were drilled on the mill shell and insulated copper conductors were glued into the holes. The copper conductors had drilled holes into which the RTDs were inserted to pick the heat transferred by the copper from the mill. A 16-channel data logger was used to convert the measured temperatures into an analogue temperature signal that was displayed on a personal computer. The following process parameters were varied during the test runs to observe their effect on the resulting temperature profile along the length of the mill from feed to discharge: (i)Slurry flow rate (2 -3l/min). (ii)Mill tip speed (1 500rpm- 2 000rpm). (iii)Media load (1.5-2.5l). A platinum ore, UG2, from Amandebult in South Africa was used for the test work at Anglo American Technical Solutions. A feed with F80 = 88μm was used for the tests. The characteristic temperature profile from the feed point to the mill discharge indicated overall plug flow behaviour with some axial mixing superimposed on the plug flow behaviour. The recirculating media and coarse particles at feed point caused a step change in temperature of the slurry as it enters the mill. The greatest temperature change within the mill was observed to occur at the first compartment of the mill. A predictive model was developed (through use of mass and energy balances) to correlate the mill variables, tip speed, feed flow rate and media load with the resulting mill temperatures. The mixing coefficients of the mill were calculated. The model can predict the degree of mixing in the mill and could be used to predict the temperature profile along the length of the mill as well, given any combination of the above three mill variables. It has been shown that use of temperature data acquisition systems has potential to improve control and monitoring of the IsaMill both operationally and from a maintenance point of view as the condition of the mill can be monitored without actually having to stop the mill but by looking at variations from the signature temperature profile.